Southeast Asia in Political Science: Theory, Region, and Qualitative Analysis - Fernando, Rolando S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 24 No 1-2 (2009): The Philippines in the WTO, 2011)
Pernicious dualisms within the social sciences, particularly in political science, have continued in recent years, albeit minimally abated and on a more polite discourse level. First and foremost is the unbearably drawn out debate between qualitative and quantitative methods that has tested the civility of even the most polite of scholars. Added to these epistemological and ontological battlegrounds are the parallel debates on “small n” versus “large n” sample sizes, interpretivism versus positivism, meaning versus causal inferences, and—more specifically within comparative politics—universal theory formulation versus nuanced area studies. Oftentimes, the core issue of establishing viable bases of comparison, qualitative bases in this volume’s case, as a key component of a sound comparative framework, is lost in the shrillness of the debate. This well-intentioned anthology is partly successful in addressing this theoretical and methodological quandary, but a significant amount of work remains.